The antiepileptic activity of JSTX-3 is mediated by N-methyl-D-aspartate receptors in human hippocampal neurons - Salamoni, S. D.; da Costa, J. C.; Palma, Mario Sergio [UNESP]; Konno, K.; Nihei, K.; Azambuja, N. A.; Neto, E. P.; Venturin, G. T.; Tavares, A. A.; de Abreu, D. S.; Breda, R. V. (Lippincott Williams & Wilkins, 2005)
We analyzed the effect of the acylpolyaminetoxin JSTX-3 on the epileptogenic discharges induced by perfusion of human hippocampal slices with artificial cerebrospinal fluid lacking Mg2+ or N-methyl-D-aspartate. Hippocampi were surgically removed from patients with refractory medial temporal lobe epilepsy, sliced in the surgical room and taken to the laboratory immersed in normal artificial cerebrospinal fluid. Epileptiform activity was induced by perfusion with Mg2+-free artificial cerebrospinal fluid or by iontophoretically applied N-methyl-D-aspartate and intracellular and field recordings of CAI neurons were performed. The ictal-like discharges induced by Mg2+-free artificial cerebrospinal fluid and N-methyl-D-aspartate were blocked by incubation with JSTX-3. This effect was similar to that obtained with the N-methyl-D-aspartate receptor antagonist DL(-)2-amino-5 phosphonovaleric acid. Our findings suggest that in human hippocampal neurons, the antiepileptic effect of JSTX-3 is mediated by its action on N-methyl-D-aspartate receptor.
Keywords: epilepsy; hippocampus; JSTX-3; N-methyl-D-aspartate receptors